Application of Taguchi Method in optimization of design darameter for turbocharger vaned diffuser - Hilmi, Amiruddin; Wan Mohd Faizal, Wan Mahmood; Shahrir, Abdullah; Mohd Radzi, Abu Mansor; R., Mamat; Azri, Alias (Emerald Publishing Limited, 2017)
Purpose – The purpose of this study is to determine the best vaned diffuser design that can generate higher pressure output at a predetermined speed.